Strange writing : anomaly accounts in early medieval China - Campany, Robert Ford, 1959- (SUNY series in Chinese philosophy and culture., 1996)
Between the Han dynasty, founded in 206 B.C.E., and the Sui, which ended in 618 C.E., Chinese authors wrote many thousands of short textual items, each of which narrated or described some phenomenon deemed "strange." Most items told of encounters between humans and various denizens of the spirit world, or of the miraculous feats of masters of esoteric arts; some described the wonders of exotic lands, or transmitted fragments of ancient mythology. This genre of writing came to be known as zhiguai ("accounts of anomalies").